Entrustable professional activities for physiotherapists to demonstrate digital health competency: an international delphi study. - Merolli, M.; Vallance, P.; McCreesh, K.; O'Sullivan, C.; Ahmed, O.; Kerry, R.; Butler-Henderson, K.; Gray, K. (Physiotherapy Theory & Practice, 2025)
Background: The physiotherapy workforce is going through a staggering period of change, amidst an evolving technological landscape. Whilst the profession has cautiously begun to embrace digital physiotherapy practice, there remains a lack of clear, evidence-based standardized guidance regarding tangible activities that demonstrate relevant clinical competence with digital health technologies in practice. Objective: Establish the world's first international consensus on entrustable professional activities (EPAs) for digital physiotherapy practice. Methods: International Delphi study of experts over three rounds, to establish consensus on digital physiotherapy practice EPAs and associated specifications. Results: Fifty-five participants completed the study (which was an 83.3% retention rate from round 1). Participants represented 16 countries. Over 50% were academics, and over 30% were clinicians. The final framework consisted of nine EPAs and 56 specifications for digital physiotherapy practice. The highest percentage rated specification was for "obtaining informed consent" for using digital health. Conclusions: This Delphi study is a seminal international consensus on the core EPAs for digital physiotherapy practice. These EPAs materialize competency. As global attention to digital health continues to increase, our workforce will need to continue to mature in this space. This international consensus will support employers, universities, peak bodies, and individual physiotherapists alike to develop alongside technology. With greater evidence and the establishment of international standards, confidence in the outcomes of digital physiotherapy practice will increase.